Relationship of Predisposing Factors to Treatment-Seeking Behavior in Lung Cancer Patients at Dr. Lung Hospital. H. A. Rotinsulu Bandung - Riasari Febriani, Handhita; Hotmaida, Linda; Widawati, Widawati (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2024)
Background: Based on 2018 Global Burden of Cancer (GLOBOCAN) data, lung cancer ranks first in the number of new cases at 2.094 million cases worldwide. Delays in treating lung cancer will worsen the patient's condition and prognosis; the higher the stage of cancer when the patient first seeks treatment, the lower his life expectancy. The causes of this delay vary from low levels of education to unaffordable medical costs; therefore, it is important to choose appropriate and appropriate treatment-seeking behavior. Objective: This study is to analyze the relationship between predisposing factors and treatment-seeking behavior in lung cancer patients in hospitals. Lung Dr. H.A. Rotinsulu, Bandung. Method: Quantitative descriptive research with a cross-sectional approach. The sample was 70 lung cancer patients using the accidental sampling technique. The independent variable is predisposing factors, which include knowledge and attitudes, and the dependent variable is treatment-seeking behavior. The instrument used was a questionnaire. The test used is Spearman's rank. Results: Knowledge and attitude factors are related to treatment-seeking behavior with each p-value of 0.02. Conclusion: There is a relationship between knowledge and attitudes and treatment-seeking behavior in lung cancer patients at Dr. H. A. Rotinsulu Bandung. Low knowledge and negative attitudes cause respondents to prefer to treat their illnesses themselves when they feel the first symptoms rather than seeking treatment at modern/medical health facilities. Modern/medical treatment will only be carried out when the respondent does not feel cured or the condition of the disease gets worse after self-medicating. Thus, providing information and education about lung cancer and behavior in seeking appropriate treatment is really needed by patients in order to choose the right place for treatment.